If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + k * 8 = 84 Reorder the terms for easier multiplication: 12 + 8k = 84 Solving 12 + 8k = 84 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 8k = 84 + -12 Combine like terms: 12 + -12 = 0 0 + 8k = 84 + -12 8k = 84 + -12 Combine like terms: 84 + -12 = 72 8k = 72 Divide each side by '8'. k = 9 Simplifying k = 9
| -52=4(5+6x) | | 142=x^2+8x | | 26=2(8+x) | | 10ab-6ab= | | 7(-7+4x)=118 | | 7(6+x)=6(x-3) | | -3(2n-3)=4(5-n) | | y-3*13=13 | | 7(C+2)=3C-5+4C+9 | | 5=4k+53 | | z/4=30 | | 2(9x-8)=19x-15 | | 5x-17=3x+10 | | 2x(5-3)-3=5 | | 4(6)+3= | | 3y+12x=-11 | | 1.1x+1.2+-5.4=-10 | | 8k(4-6)-2x=16(3-k) | | 8(2x-3)-4=6x+9x-1 | | 30x-3x=X-2 | | 6x+15-7= | | 2(2n-1)=(n+3) | | 18+8x=9(x-2) | | 2(t-6)+6t=4(2t+3)-10 | | 3(9-3x)=45 | | x-5d=3 | | 6(-4x+5)=246 | | -77=7(1+4b) | | 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) |